1975
DOI: 10.1111/j.1476-5381.1975.tb07621.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Mescaline on Activity and Emotional Defaecation in Seven Strains of Mice

Abstract: 1Mescaline hemi-sulphate (35 mg/kg body weight) was injected intraperitoneally into male mice (Mus musculus) from seven genetically diverse laboratory strains. 2 The effect of mescaline was found by comparison of the emotional defaecation and open field activity of mice after mescaline injection with the performance of the same mice after a subsequent saline (0.9% w/v NaCl solution) control injection. 3 In strains A2G, C3H/He, C57BR/cd, CBA/Cam and F/St, mescaline inhibited emotional defaecation and stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
1
2
1
1
Order By: Relevance
“…The anxiolytic-like top swimming profile evoked by mescaline in the novel tank (Fig. 1A) is consistent with its ability to decrease emotionality in mice (Lush, 1975) and increase top swimming in goldfish (Abramson et al, 1979). The drug also affected the patterning of zebrafish swimming (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The anxiolytic-like top swimming profile evoked by mescaline in the novel tank (Fig. 1A) is consistent with its ability to decrease emotionality in mice (Lush, 1975) and increase top swimming in goldfish (Abramson et al, 1979). The drug also affected the patterning of zebrafish swimming (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…While mescaline increases behavioral activity in rodents (Lush, 1975; Nakama et al, 1972; Shah, 1973; Shah, 1976), we found no difference in distance traveled or velocity between control and mescaline-treated fish in the open field test. PCP also did not affect open field behavior, in agreement with past rodent studies at similar doses (Lee et al, 2005; McLean et al, 2010).…”
Section: Discussioncontrasting
confidence: 60%
“…Such a direct effect may be unlikely, however, since most other investigations have reported reductions in defecation following administration of neuroleptic drugs in emotional animals (Allain 8i. Lechat, 1970;Brimblecombe & Green, 1962;Cox & Tye, 1975; Kameyama, Suzuki, & Nabeshima, 1980;Lush, 1975;Nabeshima et al, 1975;Suzuki et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated decreased emotional defecation by animals under the effect of drugs (Allain & Lechat, 1970;Brimblecombe & Green, 1962;Cox & Tye, 1975;Kameyama & Nabeshima, 1978;Lush, 1975;. In all of these studies, 13 the animals were tested in novel open-field environments.…”
mentioning
confidence: 99%
“…A administração de substâncias alucinógenas com ação agonista sobre receptores 5HT-2 como a mescalina é tida como potencializadora da neofobia inicial, pois suprime atividade locomotora e comportamento exploratório no campo aberto (Wing et al, 1990). Por outro lado, a supressão do comportamento exploratório e da atividade locomotora não é observada após a administração dos agonistas serotoninérgico LSD ou 2,5-dimetoxy-4-metilamfetamina quando em ambiente familiar ou após acomodação (Wing et al, 1990 (Lush, 1975).…”
Section: Análise Bioquímicaunclassified